Pengaruh Harga Jual Dan Biaya Distribusi terhadap Volume Penjualan Aspal Curah pada PT Sarana Aceh Utama di Lamreh Aceh Besar - Bukhari Usman; Darnelly Darnelly; Cut Delsie Hasrina; Nauval Julian Alfata (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2022)
This  study  aims  to  determine  the  effect  of  selling  prices  and  distribution  costs  on  the volume of bulk asphalt sales at PT. Main Aceh Facilities in Lamreh Aceh Besar. Data collection techniques in this study were carried out by means of observation, interviews and documentation. The data analysis method used is multiple linear regression analysis. The research data processing was carried out using the SPSS for windows software model. The results showed that the selling price variable partially had a significant effect on the sales volume of bulk asphalt at PT. Sarana Aceh Utama, because the t-count value is greater than the t-table value or Ha is accepted, namely (17.876 > 1.672) and the significant level is below 0.05, i.e. (0.000 < 0.05) and the distribution cost variable  partially  has  no  significant  effect  on  sales  volume  of  bulk  asphalt  at  PT.  Sarana  Aceh Utama, because the t-count value is smaller than the t-table value, namely (-3.661 <1.672) and the significant  level  is  below  0.05,  namely  (0.001  <0.05)  or  Ha  is  rejected.  The  selling  price  and distribution  cost  variables  simultaneously  have  a  significant  effect  on  the  sales  volume  of  bulk asphalt at PT. Sarana Aceh Utama, because the calculated F value is greater than the table F value, which is (1689.417 > 3.16) and the significant level is below 0.05, namely (0.000 < 0.05) or Ha is accepted.